Development and growth of the pectoral girdle and fin skeleton in the extant coelacanth Latimeria chalumnae. Issue 3 (12th November 2019) - Mansuit, Rohan; Clément, Gaël; Herrel, Anthony; Dutel, Hugo; Tafforeau, Paul; Santin, Mathieu D.; Herbin, Marc
Abstract: The monobasal pectoral fins of living coelacanths and lungfishes are homologous to the forelimbs of tetrapods and are thus critical to investigate the origin thereof. However, it remains unclear whether the similarity in the asymmetrical endoskeletal arrangement of the pectoral fins of coelacanths reflects the evolution of the pectoral appendages in sarcopterygians. Here, we describe for the first time the development of the pectoral fin and shoulder girdle in the extant coelacanth Latimeria chalumnae, based on the tomographic acquisition of a growth series. The pectoral girdle and pectoral fin endoskeleton are formed early in development with a radially outward growth of the endoskeletal elements. The visualization of the pectoral girdle during development shows a reorientation of the girdle between the fetus and pup 1 stages, creating a contact between the scapulocoracoids and the clavicles in the ventro‐medial region. Moreover, we observed a splitting of the pre‐ and post‐axial cartilaginous plates in respectively pre‐axial radials and accessory elements on one hand, and in post‐axial accessory elements on the other hand. However, the mechanisms involved in the splitting of the cartilaginous plates appear different from those involved in the formation of radials in actinopterygians. Our results show a proportional reduction of the proximal pre‐axial radial of the fin, rendering the external morphology of the fin more lobe‐shaped, and a spatial reorganization of elements resulting from the fragmentation of the two cartilaginous plates. Latimeria development hence supports previous interpretations of the asymmetrical pectoral fin skeleton as being plesiomorphic for coelacanths and sarcopterygians. Abstract : We described for the first time the development of the pectoral appendages of the living coelacanth Latimeria . The pectoral fin and girdle are form early in the development of the coelacanth. The pectoral fin shows a reorientation of its girdle and a proportional reduction of its proximal radial elements, rendering the external morphology of the fin more lobe-shaped.